Faktor Yang Mempengaruhi Mahasiswa S1 Ekonomi Islam Fakultas Ekonomi dan Bisnis Universitas Airlangga Tidak Termotivasi Menjadi Karyawan Organisasi Pengelola Zakat - Azhari, Haryo Januar; Hapsari, Meri Indri (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This research aims to determine the factors that influence Students of IslamicÂ Economics FEB UNAIR not motivated being a Zakat Organizationâs employee.This research used quantitative methods through exploratory factor analysis.Â Characteristic of the population in this research are Students of Islamic Economics FEB UNAIRÂ class 2010-2011 who following the active class. The number of samples at the time of preÂ eliminary test by conducting an interview written as many as 10 informants, and main testÂ required 90 respondents. The sampling technique used is probability sampling. Sampling wasÂ done using simple random sampling.Based on the results of study indicate that there are four factors that influenceÂ Students of Islamic Economics FEB UNAIR. The four factors as a result of reduction ofÂ processing factor analysis. These four factors named by factor of the recognition, support byÂ circles, Zakat Organizationâs image, and informations about Zakat Organization.Advice for the are improves giving more informations about Zakat OrganizationâsÂ needed employees. For academic side, can more improves more study about zakatÂ management. Factor that formed in this study can also be made henceforth researchÂ materials to influence another variable, namely interest to work at Sharia Bank.